The Impact of Dreams of the Deceased on Bereavement: A Survey of Hospice Caregivers. (March 2014) - Wright, Scott T.; Kerr, Christopher W.; Doroszczuk, Nicole M.; Kuszczak, Sarah M.; Hang, Pei C.; Luczkiewicz, Debra L.
Many recently bereaved persons experience vivid and deeply meaningful dreams featuring the presence of the deceased that may reflect and impact the process of mourning. The present study surveyed 278 bereaved persons regarding their own perspective of the relationship between dreams and the mourning process. Fifty eight percent of respondents reported dreams of their deceased loved ones, with varying levels of frequency. Most participants reported that their dreams were either pleasant or both pleasant and disturbing, and few reported purely disturbing dreams. Prevalent dream themes included pleasant past memories or experiences, the deceased free of illness, memories of the deceased's illness or time of death, the deceased in the afterlife appearing comfortable and at peace, and the deceased communicating a message. These themes overlap significantly with previous models of bereavement dream content. Sixty percent of participants felt that their dreams impacted their bereavement process. Specific effects of the dreams on bereavement processes included increased acceptance of the loved one's death, comfort, spirituality, sadness, and quality of life, among others. These results support the theory that dreams of the deceased are highly prevalent among and often deeply meaningful for the bereaved. While many counselors are uncomfortable working with dreams in psychotherapy, the present study demonstrates their therapeutic relevance to the bereaved population and emphasizes the importance for grief counselors to increase their awareness, knowledge, and skills with regards to working with dreams.